Towards the total synthesis of trichormamide A, a cyclic undecapeptide. Issue 41 (10th October 2018) - Gaillard, Michel; Das, Sanjit; Djibo, Mahamadou; Raviglione, Delphine; Roumestand, Christian; Legrand, Baptiste; Inguimbert, Nicolas
Graphical abstract: Highlights: First total synthesis of the natural product trichormamide A. Extension of the synthesis to a trichormamide A diastereomer. Trichormamide A synthesized through a SPPS and in solution cyclization process. Structures were studied by means of NMR and HRMS. Abstract: Lipocyclopeptides isolated from marine sources hold great promise as new lead for therapeutics. Here, we propose the first attempt towards the total synthesis of Trichormamide A. This synthesis will help to confirm the proposed structure of the cyclic lipopeptide.